On soliton solutions of the Wu-Zhang system - İnç, Mustafa; Kilic, Bulent; Karatas, Esra; Al Qurashi, Maysaa' Mohamed; Baleanu, Dumitru; Tchier, Fairouz (De Gruyter Open Ltd, 2016)
In this paper, the extended tanh and hirota methods are used to construct soliton solutions for the WuZhang (WZ) system. Singular solitary wave, periodic and multi soliton solutions of the WZ system are obtained.
Keywords: extended tanh method; Hirota method; WuZhang system; singulary solitary wave solution; multi soliton solution